Strategies for Advanced Oncolytic Virotherapy: Current Technology Innovations and Clinical Approaches - Qing Ji; Yuchen Wu; Andreas Albers; Meiyu Fang; Xu Qian (Pharmaceutics, 2022)
Oncolytic virotherapy is a type of nanomedicine with a dual antitumor mechanism. Viruses are engineered to selectively infect and lyse cancer cells directly, leading to the release of soluble antigens which induce systemic antitumor immunity. Representative drug Talimogene laherparepvec has showed promising therapeutic effects in advanced melanoma, especially when combined with immune checkpoint inhibitors with moderate adverse effects. Diverse viruses like herpes simplex virus, adenovirus, vaccina virus, and so on could be engineered as vectors to express different transgenic payloads, vastly expanding the therapeutic potential of oncolytic virotherapy. A number of related clinical trials are under way which are mainly focusing on solid tumors. Studies about further optimizing the genome of oncolytic viruses or improving the delivering system are in the hotspot, indicating the future development of oncolytic virotherapy in the clinic. This review introduces the latest progress in clinical trials and pre-clinical studies as well as technology innovations directed at oncolytic viruses. The challenges and perspectives of oncolytic virotherapy towards clinical application are also discussed.